Energy and binational navigation in the Uruguay River. The public poli-cies in the great infrastructure works (1938–1983) and the dam and fer-ro–automotive connection of Salto Grande - Camarda, Maximiliano (Universidad Nacional del Litoral, 2020)
The work that we present is an analysis of the moments of the cycle of public policies from deepening the binational dam of Salto Grande, on the Uruguay River, which directly involved the Argentine Republic and the Oriental Republic of Uruguay and indirectly to the Federative Republic of Brazil. This work had the objective of providing cheap energy for the development of the industry in both countries, an objective that more than agreed on the surface had to overcome considerable obstacles below it.